Allylic Azide Rearrangement in Tandem with Intramolecular Huisgen Cycloaddition for Iminosugar and Glycomimetic Synthesis: Functionalized Piperidine, Pyrrolidine, and Pyrrolotriazoles from d-Mannose - Chadda, Rekha; McArdle, Patrick; Murphy, Paul V. (Synthesis, 2017)
Intramolecular Huisgen azide-alkene cycloaddition reaction of 7-azido-hepta-1,5-diene-3,4-diols, prepared from methyl α-d-mannopyranoside, were carried out. Allylic azide rearrangement to secondary azides occurred in tandem with triazoline formation and this intermediate was then decomposed in the presence of nucleophilic reagents to give pyrrolidines, piperidines, or azepanes depending on whether cyclic constraint was incorporated or not, on diol stereochemistry and on the nucleophile. The tandem reaction worked best when aziridine formation from the triazoline was efficient, and this efficiency improved on removal of cyclic constraint. Proposals to account for the observed diastereoselectivities are provided. The allylic azide rearrangement in tandem with the intramolecular Huisgen azide-alkyne cycloaddition was also investigated from azidoheptaenyne diols and gave dihydropyrrolotriazoles. All reactions were diastereoselective, and this was high in some cases. Two X-ray crystal structural determinations, 13C NMR data, and 1D and 2D NOESY experiments were used for stereochemical assignments.
Keywords: tandem reaction; allylic azide rearrangement; azide-alkene cycloaddition; stereoselective synthesis; iminosugar; glycomimetic